Can automation reduce workplace stress? / Rosliza Md Zani and Mohd Radzi Mohd Khir - Md Zani, Rosliza; Mohd Khir, Mohd Radzi (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
The rapid growth of technology has changed the way people does business. Many organizations have automat ed their operations to stay competitive in the market. Automation refers to a process or system that can be operated automatically, without the use of labour or manpower. Automation has proven to improve job efficiency and contribute to productivity improv ement and cost reduction. Automation improves throughput, improves quality, improves process or product durability, improves output consistency, and reduces cycle time. In addition, it can replace hard, physical, or monotonous work. (Lamb, 2013